Edukasi Diet Tentang Pengetahuan dan Kepatuhan pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Biru Kab.Bone - Musdalipa Musdalipa; Najman Najman (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Diabetes Mellitus is a chronic disease characterized by high blood sugar levels due to problems with insulin production or function. In managing it, patients do not rely solely on medication but also need to properly manage their diet. Diet education is an important component to help patients understand the types, amounts, and timing of foods so that blood sugar levels can be well controlled. Patients' knowledge about a diabetes diet includes understanding recommended foods, foods that should be limited, portion control, and the importance of a balanced diet. Patients who are well-informed tend to be better at choosing healthy foods, reducing excessive sugar intake, and maintaining regular eating habits. On the other hand, a lack of knowledge can lead to uncontrolled eating patterns and increase the risk of diabetes complications. Diet adherence is the behavior of patients in following the eating instructions that have been given by. Improving these two aspects is expected to help control blood sugar levels, reduce the risk of complications, and improve the quality of life for patients with diabetes mellitus.